Aplikasi Metode Simpleks Pada Optimalisasi Biaya Bahan Baku (Studi Kasus: Ukm Najmah Klappertart): Aplikasi Metode Simpleks Pada Optimalisasi Biaya Bahan Baku (Studi Kasus: Ukm Najmah Klappertart) - Resnawati; Damayanti, D; Jaya, A I (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
ABSTRACT The purpose of this research is to obtain an the optimal production costs of Klappertart based on the basic ingredients comparing the production cost of Klappertart in Najmah Klappertart with production costs using the simplex method. The result showed that the optimal costs is ,-. This result is equal to the total cost of klappertart by SMEs Najmah Klappertart, so it can be concluded that the cost of production klappertart based on the basic ingredients on SMEs Najmah Klappertart were optimal. Keywords : Optimal Cost, Basic Ingredients, Production Costs. (A-Z), Simplex Method